Implementasi Collaborative Coaching Pada Kinerja Guru SDN Penambuhan - Arif Budiono; Sri Surachmi; Gunawan Setiadi (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to describe the use of collaborative coaching on teacher performance. This research was conducted from July 2022 to August 2022. The research method used was descriptive qualitative research with a phenomenological approach. Sources of data were obtained from school principals, classroom teachers and mulok teachers. Data collection techniques using interviews. The data analysis technique used is John W. Creswell's qualitative data analysis (2017). Based on the results of the analysis, it shows that collaborative coaching on teacher performance is in accordance with the steps of the GROW collaborative coaching model, namely asking the purpose of doing coaching, encouraging coachees to expand their point of view related to the situation at hand, agreeing on the desired results in overcoming problems, discussing the most effective way to achieve a destination.